2015
DOI: 10.1128/aem.03916-14
|View full text |Cite
|
Sign up to set email alerts
|

Impact of the Use of β-Lactam Antimicrobials on the Emergence of Escherichia coli Isolates Resistant to Cephalosporins under Standard Pig-Rearing Conditions

Abstract: The aim of this study was to evaluate if the treatments with ceftiofur and amoxicillin are risk factors for the emergence of cephalosporin resistant (CR) E. coli in a pig farm during the rearing period. One hundred 7-day-old piglets were divided into two groups, a control (n ‫؍‬ 50) group and a group parenterally treated with ceftiofur (n ‫؍‬ 50). During the fattening period, both groups were subdivided in two. A second treatment with amoxicillin was administered in feed to two of the four groups, as follows: … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
28
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 31 publications
(28 citation statements)
references
References 32 publications
0
28
0
Order By: Relevance
“…In particular, in veterinary medicine, ceftiofur and cefquinome are specifically used to treat respiratory diseases and exudative epidermitis, and meningitis, respectively. Cefquinome had MRL values more restrictive than those of ceftiofur (50-200 µg/kg vs. 100-6000 µg/kg) [2], but the use of ceftiofur must be carefully evaluated as its use could develop E. coli resistance [85,86].…”
Section: β-Lactam Antibioticsmentioning
confidence: 99%
“…In particular, in veterinary medicine, ceftiofur and cefquinome are specifically used to treat respiratory diseases and exudative epidermitis, and meningitis, respectively. Cefquinome had MRL values more restrictive than those of ceftiofur (50-200 µg/kg vs. 100-6000 µg/kg) [2], but the use of ceftiofur must be carefully evaluated as its use could develop E. coli resistance [85,86].…”
Section: β-Lactam Antibioticsmentioning
confidence: 99%
“…Feeding waste milk (WM) to dairy calves increased the prevalence of resistant bacteria to the antimicrobials used in the farm, but also to other antimicrobials that were not used (Aust et al, 2013;Pereira et al, 2014a;Maynou et al, 2017). Cameron-Veas et al (2015) demonstrated the capacity of resistant strains to transfer β-lactam resistance genes to other bacteria by conjugation in pigs parentally treated with ceftiofur (EFT). In this study, the transconjugants also exhibited resistance to antimicrobial classes other than β-lactams, suggesting co-selection of resistance genes by genetic linkage to others.…”
Section: Introductionmentioning
confidence: 99%
“…However, although the use of broad-spectrum cephalosporins has been implicated in the emergence of resistance (15,16), few studies demonstrated a clear association between amplification of resistance and drug exposure. Animal studies in pigs found an increase in the prevalence of resistant E. coli within the first week of treatment with ceftiofur and amoxicillin (11). Similar studies in calves showed a 14% increase in fecal bacteria resistant to ceftriaxone within 3 days after treatment.…”
Section: Discussionmentioning
confidence: 71%
“…Previous studies found a relationship between the qPCR ratio and surveillance cultures, indicating that this ratio reflects colonization by resistant bacteria. Antibacterial treatment may select for a wide range of cephalosporin resistance genes from different families and microorganisms (11,12). In the present study, we studied the effect of antibiotic treatment on bla CTX-M genes normalized by the total bacterial load by using the 16S rRNA genes with a method developed earlier (9).…”
Section: Discussionmentioning
confidence: 99%